Soybean yield and nutrition after tropical forage grasses - Costa, Nídia Raquel [UNESP]; Andreotti, Marcelo [UNESP]; Crusciol, Carlos Alexandre Costa [UNESP]; Pariz, Cristiano Magalhães [UNESP]; Bossolani, João William [UNESP]; Pascoaloto, Isabô Melina [UNESP]; da Rocha Lima, César Gustavo [UNESP]; dos Santos Batista Bonini, Carolina [UNESP]; de Castilhos, André Michel [UNESP]; Calonego, Juliano Carlos [UNESP] (Springer Nature, 2021)
In tropical agroecosystems, intercropping crops and including perennial forages can increase crop system diversity and sustainability. However, adequate management of cash crops in crop rotation under no-till requires an understanding of the release of nutrients by surface mulch. This study evaluated the effects of two sowing times and nitrogen (N) management of palisade grass [Urochloa brizantha (A. Rich.) Stapf Marandu] and guinea grass [Megathyrsus maximus (Jacq.) B.K. Simon & S.W.L. Jacobs Tanzania] on forage production, nutrient accumulation, and decomposition rates; soybean [Glycine max (L.) Merrill] yield; and soil chemical properties over three growing seasons. Palisade and guinea grasses were sown for intercropping with sorghum [Sorghum bicolor (L.) Moench] in the growing season or after sorghum silage harvest (hereafter succession) and subjected to N fertilization management (urea − 0 and 70 kg N ha−1 cut−1, totalling 210 kg N ha−1 per season) during the off-season. Nitrogen fertilization increased nutrient accumulation in surface mulch in all cropping systems. Regardless of cropping system, N rates, or growing season, palisade and guinea grass provided an adequate plant biomass production, soil cover throughout the year, soybean nutrient use efficiency, and soil quality. Soybean was positively influenced by N fertilization of grasses sown in succession to sorghum. Guinea grass had the greatest effect on soybean grain yield, with an improvement of 0.8 Mg ha−1. Sowing grasses in succession to sorghum positively affected soil pH, Ca, Mg, and base saturation.
Keywords: Glycine max (L.) Merrill; Megathyrsus maximus; Remaining straw decomposition; Sustainable agroecosystem; Tropical agriculture; Urochloa brizantha